Development of Arabic Language Learning Based on CALL (Computer Assisted Language Learning) and Flash Cards - Aisyah Maimunah; Moh. Khasairi; Irhamni Irhamni (Jurnal Iman dan Spiritualitas, 2026)
This research aims to develop Arabic language teaching materials based on Computer-Assisted Language Learning (CALL), utilizing the Moodle platform. Moodle will incorporate vocabulary, reading texts, dialogues, and exercises tailored to the curriculum of MTs Al-Muslihuun Tlogo Blitar. Additionally, Moodle will include images, animations, and online quizzes related to the speaking skill (maharah kalam). This CALL implementation will be integrated with vocabulary games in the form of Flashcards. The research employs the ADDIE model developed by Reiser and Margareth Mollenda. The Moodle platform is designed by analyzing the needs for teaching materials, referring to the independent curriculum for the ninth grade of Madrasah Tsanawiyah under the Ministry of Religious Affairs. The embedded videos are sourced from YouTube.com, while animations are obtained from social media platforms. Exercises and Flashcards are designed using Canva.com premium and Adobe Photoshop Lightroom. Quizzes are created using Quizizz.com, Kahoot.com, Owl Quiz, Wordwall, Fyrebox, and Baamboozle. The product trial demonstrated student acceptance and satisfaction, achieving a rate of 93.5%. Summary of statistical results: There was an increase in the average value (mean) between the pre-treatment and post-treatment periods. The initial mean value, measured through the pre-test, was 60.22, while the post-test mean value, following the treatment, showed a significant increase to 78.70. That indicates that the intervention had a positive effect.